Network-Constrained Multiperiod Auction for Pool-Based Electricity Markets of Hydrothermal Systems - Pereira, Augusto Cesar [UNESP]; Oliveira, Alberto Quialheiro de [UNESP]; Baptista, Edmea Cassia [UNESP]; Balbo, Antonio Roberto [UNESP]; Soler, Edilaine Martins [UNESP]; Nepomuceno, Leonardo [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2017)
Network-constrained market clearing procedures in pool-based electricity markets of hydropower systems have traditionally neglected the constraints associated with physical and operating aspects of hydroelectric generation (hydraulic constraints). Such constraints are generally taken into account by means of expost procedures, which may lead to suboptimal results regarding social welfare function. This paper proposes a network-constrained auction model for hydrothermal systems that represents the hydraulic constraints in detail. The objectives of the paper are twofold: the analysis of the impact of hydraulic constraints on market clearing prices and on generation/consumption scheduling and the analysis of the influence of strategic offering of hydro plants in the operation of a hydraulic cascade. As some of the hydraulic constraints are nonlinear and intertemporal, linearization techniques are applied, resulting in a mixed-integer linear programming problem.
Keywords: Hydrothermal systems; linearization; market clearing procedure; mixed-integer linear programing